Impact Of Personal Selling In Efforts To Increase Sales Volume - Enny Istanti; Indriana Kristiawati; Achmad Daengs GS; Anis Yuli Astutik (International Journal of Economics, Commerce, and Management, 2025)
Competition in Indonesia’s business world today compels companies to strategize in order to outperform their rivals. Only those companies that are truly strong, implement competitive strategies correctly, and carry out intensive promotions will succeed. One promotional tool that is expected to directly establish, improve, dominate, or maintain mutually beneficial exchange relationships with customers is personal selling, particularly aimed at encouraging consumers to purchase the offered products.A company’s goal is to obtain maximum profit from its business operations. To achieve this, managerial expertise and capability are required to combine the functions within the company effectively. Personal selling is carried out by the company to introduce its products, influence and inform consumers, so they are encouraged to buy—ultimately increasing sales volume.This study seeks to examine whether personal selling has a significant impact on increasing sales volume at PT. Intermas Tata Trading, Surabaya branch. A qualitative approach is used, supported by both qualitative and quantitative data from the company. Data collection techniques include editing, tabulating, and interviews. Data processing involves simple correlation analysis, simple regression analysis, and t-tests. Hypothesis testing is conducted using statistical analysis with SPSS 16.0.The study results confirm that the hypothesis is true: the personal selling variable (X) has a significant influence on the sales volume (Y) at PT. Intermas Tata Trading, Surabaya. This is evidenced by the t-value (4.005) > t-table (2.228) at a significance level of 0.002. The simple correlation coefficient is 0.785 or 78.5%, indicating a very strong and positive relationship between the independent variable (personal selling) and the dependent variable (sales volume).